The clinical application of Chinese herbal medication to depression: A narrative review - Kang, Dongyu; Dong, Huixi; Shen, Yidong; Ou, Jianjun; Zhao, Jingping (Frontiers in Public Health, 2023)
Depression severely impairs psychosocial functioning and quality of life, which places a huge burden on patients and their families. However, the physiological mechanism of depression remains unknown. Treatment with existing antidepressant medications is effective in around 50% of patients according to various studies, but is associated with severe side effects including nausea and headaches. Chinese herbal medicine (CHM) has been approved and widely used for depression as an alternative medicine in Chinese culture for decades. It has certain advantages and potential in the prevention and treatment of depression. In this review, we summarize the currently available evidence for the efficacy of CHM for the treatment of depression and physiological diseases comorbid with depression. We further discuss the possible mechanisms of action of CHM and the relationships to our current understanding of depression. The majority of current evidence has suggested that the combined treatment with CHM and mainstream antidepressants improves the response rate and reduces the side effects, while CHM alone could be more effective than placebo. However, the results should be carefully interpreted due to the shortcomings of existing clinical trials and a high risk of bias in meta-analyses. Our review provides a summary of the current applications and understanding of widely used CHMs for depression.